(untitled) (mathematica didactica, 2020)
Central goal of mathematical learning is to develop an understanding of geometrical thinking. Little is known, how children think, handle und describe their thoughts when working on geometric tasks and how their understanding can be supported. This research is done by the teaching-learning-lab ZahlenRaum which connects empirical scientific research and the explorative research-based learning of teacher students. On the one hand, this article presents first results of children’s concept formation of (congruent) triangles and on the other hand it shows how these local theories become the subject of research-based learning by teacher students in the next development cycle.